Pengembangan Media Pembelajaran Fisika Interaktif Berbasis Etnosains untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Afifatuz Zumrotin; Ahmad Harjono; Nina Nisrina (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to develop an ethnoscience-based interactive physics learning media on sound waves that is valid and practical to support students' critical thinking skills. The development of the learning media was motivated by the fact that physics instruction remains predominantly conventional and has not yet integrated local culture as a contextual learning resource. The developed media integrates the concept of sound waves with the local culture of Lombok, particularly the Gendang Beleq tradition, using Articulate Storyline 3. This research employed a Research and Development (R&D) approach based on the 4D model, consisting of the define, design, and develop stages. The resulting product was an ethnoscience-based interactive physics learning media accompanied by supporting instructional materials. Product validation was conducted by three expert validators and two practitioner validators. The practicality test involved 17 students of class XI MIPA B and two physics teachers at SMAN 10 Mataram. The research instruments included validation sheets, reliability sheets, and response questionnaires for both students and teachers. The results showed that the learning media achieved a validity score of 91.11% from expert validators and 98.33% from practitioner validators, both categorized as highly valid. The critical thinking skills instrument obtained validity scores of 91.67% from expert validators and 95.00% from practitioner validators, both categorized as highly valid, with a reliability score of 95.71%, indicating a reliable instrument. The practicality test results showed student and teacher response scores of 93.16% and 98.13%, respectively, both categorized as highly practical. Therefore, the developed learning media is considered feasible for use in physics learning.